0.5-V High Linear Fully Differential Multiple-Input Bulk-Driven OTA With Effective Self-Embedded CMFB - Fabian Khateb; Tomasz Kulej; Montree Kumngern; Pipat Prommee (My University, 2024)
This paper presents a new fully differential multiple-input operational transconductance amplifier (FD MI-OTA) with an effective self-embedded common-mode feedback circuit (CMFB). The circuit employs several design techniques to extend the linearity to the rail-to-rail level, such as a bulk-driven, multiple-input capacitive voltage divider and source degeneration. The circuit uses self-cascode transistors to increase the gain of the OTA from one side and to create a common-mode feedback circuit, needed to control the common-mode output voltage from the other side. Thus, the CMFB is part of the OTA and as a result, its chip area and power consumption remain unchanged. The performance of the proposed circuit was simulated using TSMC's CMOS 0.18 μm process in the Cadence Virtuoso System Design Platform to validate the performance of the topology. Intensive simulation results based on Monte Carlo and process, voltage, temperature corners were performed to confirm the OTA's performance and the robustness of the CMFB. The circuit operates with a supply voltage of 0.5 V and consumes 17.5nW of power, making it suitable for applications with extremely low voltage supply and low frequency. As an application, a second-order low-pass filter was designed based on the proposed FD MI-OTA.
Keywords: Operational transconductance amplifier; Process corners; Transconductance; Linearity; Analog and Mixed-Signal Circuit Design